Foundations of sport and exercise psychology - Weinberg, Robert S; Gould, Daniel (b)
This text captures the world of sport and exercise psychology. It not only explains the basic concepts and principles in the field, but it also shows how they apply to counseling, teaching, coaching, sport medicine and fitness instruction." "Foundations of Sport and Exercise Psychology (Second Edition) contains visuals, anecdotes, case studies, critical thinking questions, and references."--Jacket.
Includes bibliographical references (p. 511-528) and index.
Keywords: Sports -- Psychological aspects; Exercise -- Psychological aspects